New ways of developing Russian avant-garde idioms: a corpus-based approach - Irina V. Zykova (Russian Language Studies)
The research studies the functioning of Russian avant-garde idioms, a unique group in the lexical-phraseological system of the Russian language, which formed at the beginning of the 20th century in language experiments by of the early avant-garde representatives (Cubo-Futurists). The relevance of the research is determined by linguists’ constant interest in the fundamental issues of the general theory of phraseology, reproduction (in a broad sense) of phraseological units in various discourses, their variability and modification, as well as the need for a comprehensive analysis of the foundations of certain classes of set figurative units and their role in the renewal and development of the Russian phraseological system. The purpose of the study is to establish, by means of the corpus analysis, the directions of distribution and the spheres of functioning of verbal idioms that make up the core of the Russian avant-garde idiomatics; to identify the nature, forms, or ways of their structural, semantic, grammatical, and pragmatic changes for over one century. Four avant-garde idioms were selected as the research material: заумный язык (beyond-sense language), самовитое слово (the self-sufficient word), пощечина общественному вкусу (a slap in the face of public taste), and (с)бросить коголибо с парохода современности (to throw someone off the steamer of modernity) . Their functioning was studied on the material from Russian National Corpus with the help of the elaborated analysis algorithm. The author proves that avant-garde idioms which appeared in the Cubo-Futurists’ manifestos, articles, poems, speeches, etc. have been spreading in different types of discourse (newspaper discourse, journalistic discourse, social networks, etc.). Accordingly, they are understood and developed in new ways. The main strategies of their modification in discourse, leading to their semantic, grammatical, etc. transformations, include the insertion of new components, the combination with other figurative means, the splitting of their basic form, the recomposition, the pre- and/or postpositional augment of new components, and double actualization. The corpus analysis clarifies the mechanisms of the adaptation of avant-garde idioms to the pragmatic tasks of a certain discourse, as well as the factors that determine their transition from avant-garde discourse to general linguistic usage or, conversely, to more specialized discourses, e.g. political, legal, memoir, or educational ones. The results obtained can be used in lexicographic practice.